Protective effect of brine-salt curing on physico-chemical attributes on the taki fish (Channa punctatus) and the tengra fish (Mystus tengra) at room temperature (Bangladesh Journal of Zoology, 2015)
Brine salt curied (BS) Taki fish and the small Tengra fish were studied to observe such salting procedure on their bio-chemical composition stored at room temperature (26-320C). In fresh-processed condition, moisture, protein, fat, ash, pH and free fatty acid were 62.28%, 18.02%, 2.76%, 17.24%, 6.8 and 0.5% in BS taki fish and 57.35%, 15.3%, 6.84%, 20.8%, 5.9 and 0.9%, respectively in tengra. The value of moisture, pH and FFA increased significantly (p